1994
DOI: 10.1182/blood.v83.11.3160.3160
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel receptor tyrosine kinase gene, STK, derived from enriched hematopoietic stem cells

Abstract: To identify the novel receptor tyrosine kinases (RTKs) critical to the proliferation of hematopoietic stem cells, we performed polymerase chain reaction-based cloning from highly purified murine hematopoietic stem cells. Lineage marker-negative, c-KIT-positive, and Ly6A/E- or Sca- 1-positive (Lin-c-KIT+Sca-1+) cells were sorted by a fluorescence- activated cell sorter. Two sets of degenerate oligonucleotide primers were directed to the conserved sequences of the catalytic domain, and were used to amplify cDNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Several hybridizing cDNA clones were isolated and sequenced. The sequence of the longest of these cDNAs (2,100 bp) covered nucleotides 2,634-4,720 on the full-length mouse ron cDNA sequence reported recently by Iwama et al (1994). A 1.0 kb murine ron cDNA fragment (nucleotides 2,634-3,659) was used to generate [36Sl-labelled antisense riboprobes, which were used for in situ hybridization experiments on serial sections of mouse embryos and fetuses at each gestational day from 8.5 to 18.5 days post-coitum (dpc), as well as on newborn specimens.…”
Section: Developmental Expression Pattern Of the Ron Genementioning
confidence: 88%
See 1 more Smart Citation
“…Several hybridizing cDNA clones were isolated and sequenced. The sequence of the longest of these cDNAs (2,100 bp) covered nucleotides 2,634-4,720 on the full-length mouse ron cDNA sequence reported recently by Iwama et al (1994). A 1.0 kb murine ron cDNA fragment (nucleotides 2,634-3,659) was used to generate [36Sl-labelled antisense riboprobes, which were used for in situ hybridization experiments on serial sections of mouse embryos and fetuses at each gestational day from 8.5 to 18.5 days post-coitum (dpc), as well as on newborn specimens.…”
Section: Developmental Expression Pattern Of the Ron Genementioning
confidence: 88%
“…A mouse skin cDNA library in XZAP-XR was purchased from Stratagene (La Jolla, CA) and screened under low stringency conditions with a 1 kbp human ron cDNA probe encompassing the sequences coding for the tyrosine kinase domain, the transmembrane region, and part of the extracellular domains (nucleotides 2,461 to 3,444, Ronsin et al, 1993). Four hundred thousand plaques were screened, allowing isolation of 3 positive clones, the longest corresponding to nucleotides 2,6344,720 of the published mouse sequence (Iwama et al, 1994).…”
Section: Experimental Procedures Cdna Cloning and Sequencingmentioning
confidence: 99%
“…In contrast, the Axl/Tyro3/Mer family of receptors [5,6] contains two Ig-like domains and two fibronectin type III repeats in the ectodomain and a contiguous kinase domain with two tandem tyrosines in the activation loop. The murine STK/human RON receptor [7,8], a member of the MET family of RTKs, is closely related to the Tyro3 family and shares a similar kinase structure. The ectodomain of STK, however, is composed of a disulfide-linked extracellular ␣ chain and transmembrane ␤ chain, the structure of which is poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to c-kit and flk-2, RNA encoding for a number of tyrosine kinases has been identified in haemopoietic progenitor cells. In a recent study, Iwama et al (1994) identified genetic material coding for 20 receptor and nonreceptor tyrosine kinases using reverse transcriptase polymerase chain reaction to analyse RNA of lineage negative, c-kit + murine haemopoietic stem cells. That study identified a novel tyrosine kinase gene, STK, as a member of a subfamily of receptor tyrosine kinase genes that included c-MET, c-SEA and the human homologue of STK, RON.…”
Section: Discussionmentioning
confidence: 99%